Developing English and sign language module for hearing impaired students at SEN School Idayu 1 Malang - Putera, Alam Aji; Twingardi Syahriar, Muhammad Iqbal; Mubarok, Moh. Najib; Fachriyan, M. (Journal of English Language Teaching and Learning (JETLE), 2025)
This study aimed to develop an English and sign language module for hearing-impaired students, addressing significant gaps in existing educational resources tailored to their unique learning needs. Despite the importance of effective communication for this demographic, there remains a scarcity of comprehensive materials that integrate both English language skills and sign language, particularly at the elementary level. The researchers employed the ADDIE model Analyze, Design, Develop, Implement, and Evaluate to create a module specifically designed for 15 hearing-impaired students at Grade 4 SEN School Idayu 1, Malang City. Validation was conducted through feedback from an English lecturer and a hearing-impaired students’ teacher, alongside student responses post-implementation. The results indicated that this module not only meets the academic needs of the students but also enhances their English skills, particularly in vocabulary acquisition and comprehension through the use of sign language. This study underscores the necessity for targeted educational tools that facilitate effective learning environments for hearing-impaired students, ultimately contributing to their language development and academic success.